The Effect of the Fed Interest Rate and Inflation on the Composite Stock Price Index - M. Habiburrahman; Rayhan Witra Pratama; Celia Zilfitri; Saipul Azis; Edwin Jeri; Bintang Bintang; Nuraiman Nuraiman; Cici Isma Putri (Journal of Islamic Economics and Finance Studies, 2025)
Composite Share Price Index (IHSG ) is an indicator that generally reflects the tendency of stock price movements on the Stock Exchange. In this study there are several main issues to be discussed, namely: how much influence the Fed interest rate has on the IHSG), how much influence the Inflation rate has on the (IHSG) and how much influence the Fed interest rate and Inflation has on the Composite Share Price Index (IHSG). This research is a quantitative study using descriptive analysis method with associative approach that is connecting between two or more variables. This study uses secondary data, namely data obtained from available sources such as journals, books, or the internet. While data collection techniques from books and articles and other relevant sources to obtain data that can be used as a foundation related to the object in the study. The data used is annual time series data, and processed using Eviews 7.1. Simultaneously, the results of this study indicate that the Fed interest rate and Inflation on the (IHSG) for the period 2006-2015 have a negative and insignificant effect with a probability F-statistic value of 0.106550. Partially regression results at the real level of 0.05, the Fed interest rate has a negative and insignificant effect on the (IHSG ) with a coefficient of -432.2465 and a probability value of 0.1224, inflation has a negative and insignificant effect on the (IHSG ) with a coefficient of -22.85330 with a probability of 0.8981.